Осново- та словоскладання в казначейській терміносистемі - Васковець, Людмила; Vaskovets, Lyudmyla (Східноєвропейський національний університет, 2013)
Статтю присвячено ролі основоскладання та словоскладання у казначейській терміносистемі. З’ясовано основні диференційні ознаки, притаманні складним термінам. Здійснено класифікацію складних номінативних одиниць казначейської лексики. Виокремлено юкстапозити, композити, абревіатури казначейської термінолексики, описано їхні різноманітні модифікації. The article is dedicated to the role of world-building and basis-building in treasury terminology. It is found that complex terms have basic differential features as formal and semantic amalgamation. In is investigated that complex terms express new concepts fully new concepts and we have saving of language tools thanks to the combination of brevity and semantic concentration. The classification of complex nominative units of the treasury vocabulary is realized. In the structure of treasury terminology the yukstapozites, composites, abbreviations are marked out and their different modification are described. In the article noted that the concentration of loanwords in modern Ukrainian language stimulate the starring up basses’ combining method.
The World-building and Basis-building in Treasury Terminology
Keywords: словоскладання; основоскладання; композити; юкстапозити; абревіатури; word-building; bases-building; composites; yukstapozites; abbreviations